Rezension von: Haasis, Hellmut G., Joseph Süß Oppenheimer, genannt Jud Süß - Kottmann, Ingeborg (Württembergisch Franken, 2000)
Hellmut G. Haasis, Joseph Süß Oppenheimer, genannt Jud Süß. Finanzier, Freidenker, Justizopfer, Reinbek (Rowohlt) 1998. 478 S„ Abb.